A study on competitiveness rivalry and services of technology development in Port Klang: Case study in Westport, Malaysia - M., Nik Azli; J., Jagan; M.S., Roszita; A.H ., Saharuddin (2010)
Government usually plays an important role in the environment of business competition. One perspective might be the government regulations have governed the rules of game as an environment for business to follow and fairness and efficiency are two guiding principles to establish certain appropriate rules and games.This study is aim to identify the main competitor and services of technology development that were influencing the competitiveness at Westport, Malaysia. The response from the respondents from the Westport will gain to verify the main objective of this research.Beside that, this research will identify the political, social and economic factors that caused the competitiveness among rivalry and the services of technology development. The first method is by obtaining data from secondary sources such as books, articles from journals, internet, magazines and newspapers.The second method is by using survey questionnaire. The survey questionnaire will be distributed to employees, which had interactions with maritime organization at Westport. The survey research will be conducted to gain the outcome of overall the objective from respondents.Furthermore, this research will provide some recommendation to upgrade the quality of competitiveness and the services of technology development at Westport.